Does Urbanization Promote Regional Industrial Environmental Efficiency? A Comparison of Economic Development-Oriented Regions and Environmental Governance-Oriented Regions - Sun, Liangping; Li, Leiming; Li, Yongqing; Liu, Bingquan (Frontiers in Energy Research, 2020)
Promoting industrial environmental efficiency (IEE) has attracted great concern of scholars and policymakers. Previous studies have focused on the driving factors of IEE without considering the leader-follower relationship between two stages of IEE, and used aggregated indicate to detect the effect of urbanization on IEE. In this study, we break the ‘black box’ of IEE and regard it as a serial system including economic development (ED) stage environmental governance (EG) stage, and select some typical provinces belong to ED-dominated regions and EG-dominated regions. We quantified the IEE by using slacks-based model (SBM), decomposed the effect of urbanization into 4 typical factors and detected the effect of urbanization-related factors by using Tobit regression model, then compared the IEE and effect of urbanization-related factors between different types of regions. The results show that: Overall, the IEE in different regions was low and fluctuated in 2011-2015, and it increased in ED-oriented regions while kept stable in EG-oriented regions. The IEE of ED-oriented regions was always higher than that of EG-oriented regions with the gap getting larger and larger. The IEE of two stages changed differently in each type region. Urbanization-related factors had different effects on IEE of different stages in two types of regions. Even, the same factor had significantly different effect on different regions.